Hurdiid radiodontans from the middle Cambrian (series 3) of Utah - Pates, S; Daley, A; Lieberman, B (Paleontological Society, 2017)
—Radiodontan body elements, some belonging to Peytoia and Hurdia and some unassigned, have been reported from the Langston Formation (Spence Shale Member), Wheeler Formation, and Marjum Formation of the middle Cambrian (Series 3) of Utah. These identifications are reassessed in light of recent work on the morphology of the radiodontan Hurdia. New specimens of Hurdia are identified from the Spence Shale, representing mouthparts (oral cones), cephalic carapace H-elements, frontal appendages and a single isolated swimming flap. The shape of the H-elements allows H. victoria to be identified from the Spence Shale for the first time. The flap is larger and more complete than any reported from the Burgess Shale, and allows for a better understanding of the morphology of Hurdia swimming flaps. A 3D model of a Hurdia frontal appendage indicates that there is only one morph of Hurdia frontal appendage found in both species, and apparent morphological differences between disarticulated appendages reflect a preservational continuum caused by varying oblique angles relative to the seafloor. Peytoia should no longer be reported from the Spence Shale, but its presence is confirmed in the Wheeler and Marjum formations. New mouthparts (oral cones) of Hurdia from the Spence Shale and Peytoia from the Marjum Formation with surface textures of sub- millimeter diameter raised nodes are described. These new features have not been observed in material from the Burgess Shale, and suggest slight differences in preservation.